“The pursuit of happiness”: pleasure and leisure through counterfeit branded fashion goods consumption - Rosely, Nurhidayah; Raja Yusof, Raja Nerina; Hashim, Haslinda; Adzharuddin, Nor Azura (NUN Gemilang Enterprise, 2021)
The rising demand for counterfeit goods has led to a new phenomenon in consumer behaviour. Previously, consumers’ involvement in counterfeit consumption is driven by the indistinguishable physical characteristics between the original and counterfeit versions, which allows consumers to exhibit an aspired social status position. However, current trends discovered consumers who voluntarily involve in counterfeit consumption practice are looking for pleasure maximization through leisure consumption activity, which they believed contributes to hedonic well-being. This paper, which is based upon a phenomenology study, seeks to uncover a rich and contextualised account of consumer consumption experiences, which elucidated a range of meanings on consumers’ involvement in counterfeit consumption. The consumption experiences of 12 consumers on the purchase of counterfeit branded fashion goods were gathered through in-depth interviews and analysed. The data was analysed into the thematic analysis, and two themes emerge from this study; dedication and satisfaction describe the fulfilment of consumer’s autonomous needs. Overall, this study contributes knowledge to the area of counterfeit branded fashion goods and consumer behaviour as the emerging themes describes the actual experiences captured from the consumers who were continuously involved in counterfeit consumption practice. This research contributes to scholarly and managerial knowledge from the hedonic and experiential dimensions, especially in the Malaysian context, to gain more insights into comprehending the underlying causes of counterfeit consumption phenomena.